Teacher preparation in Scotland - Shanks, Rachel (Emerald studies in teacher preparation in national and global contexts., 2020)
This book argues that knowledge management and HRM systems should be integrated. This integration provides the foundation for designing knowledge-oriented high-performance HR practices.